Analisis Tren Laporan Keuangan dan Peramalan Pendapatan Agripreneurship di SMKN PP Lembang - Danestiara, Venia; Nugraha, Arif Bakti; Pangestu, Idham Azis; Saputra, Naufal Fajar; Putra, Raka Deny Adi (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The activity "Trend Analysis for Financial Reports and Income Forecasting in the Agripreneurship Sector at the Negeri Lembang Agricultural Development Vocational School" aims to provide a basic understanding of digital technology that can be applied in the agribusiness sector, increase students' insight and readiness in facing challenges and opportunities in the Agripreneurship 4.0 era, provide practical skills in using technology in production, marketing and agribusiness management, and facilitate students in designing digital technology-based business strategies in agribusiness. Apart from that, the expected result after carrying out the seminar on Trend Analysis for Financial Reports and Income Forecasting in the Agripreneurship Sector is to provide a basic understanding of technology and be able to utilize tools such as SPSS and Google Sheet to increase productivity and efficiency in identifying challenges and opportunities in the agripreneurship sector for students at the Lembang State Agricultural Development Vocational School.